Pre-operative Serum Albumin Predicts Native Liver Survival in Biliary Atresia - Kakeru Machino; Kotaro Mimori; Seiya Ogata; Yosuke Minami; Hirofumi Shimizu; Michitoshi Yamashita; Hideaki Tanaka (Wolters Kluwer Medknow Publications, 2024)
Background: To predict native liver survival (NLS) after Kasai portoenterostomy (KP) for biliary atresia (BA) using pre-operative clinical data. Materials and Methods: Pre-operative data were collected from 29 patients with BA who underwent KP at our department between 1989 and 2017 and were analysed including serum albumin, bilirubin, prothrombin time-international normalised ratio, body height, body weight, age at KP, paediatric end-stage liver disease score calculated using the pre-operative data and the period of NLS. Results: The 10-year NLS rate of all patients was 51%. A multivariate analysis revealed that among all factors, the pre-KP serum albumin level was the only independent predictor of NLS (P = 0.04, hazard ratio = 0.269, 95% confidence interval = 0.077-0.934). The area under the receiver operating characteristic curve for NLS, determined using pre-KP serum albumin was 0.760 and 3.75 mg/dl was selected as the cut-off value. There was a significant difference in NLS between patients with high (≥3.8 mg/dl) and low (≤3.7 mg/dl) pre-KP serum albumin (90.0% vs. 31.5%, P < 0.01). Conclusions: Decreased pre-KP serum albumin may reflect not only functional impairment of the liver, but also the inflammatory process, which is hypothesized to occur during its advancement. The pre-KP serum albumin level may be a good prognostic factor for NLS in post-KP BA patients.